Audit of Governance and Service Management of Unisnu Jepara's Library Information System (SIPERPUS) Using ITIL V4 Based on Website - Nuradira, Afrida Hilda; Azizah, Noor; Minardi, Joko (Universitas Negeri Semarang, 2025)
Purpose: This research aims to assess the maturity level of governance and service management in the Library Information System (SIPERPUS) at UNISNU Jepara. The objective is to identify strengths and gaps, ensuring better alignment with ITIL V4 best practices. Methods: The research was conducted using a qualitative methodology that incorporated a literature review, user questionnaires, and the creation of a web-based audit application designed specifically for this study. Service practices such as Service Request Management, Service Desk, Change Control, and Service Catalog Management were evaluated using the ITIL V4 framework. Result: The findings indicate that SIPERPUS has independently attained a managed maturity level with well-defined Service Request Management and Service Desk practices. Additional work is required to improve Change Control and Service Catalog Management to increase process integration and make information clearer. The new web-based audit application described in this study demonstrates its capability to systematically evaluate, produce data-based recommendations, and continuously improve digital library services. Novelty: This study introduces a new web-based audit application that conforms to ITIL V4, providing an efficient and reliable alternative to manual audit methodologies. The tool significantly reduces audit time, enhances operational efficiency, and optimizes user satisfaction while improving overall service quality. The study adds to the literature on IT governance audits, specifically in higher education, and presents a scalable approach for institutions striving to meet the standards of Society 5.0.